Analyzing anomalous events in passageways with high-frequency ship signals - Cherryl Chico; Macario O. II Cordel; Mahinthan Joseph Mariasingham; Elaine S. Tan (PLoS ONE, 2025)
Passageways are critical gateways in maritime trade, providing efficient routes for global commerce. This means that disruptions such as natural disasters or human error at these crucial points can significantly impact numerous economies across various facets of trade. Thus, real-time monitoring of such events and their impact on different vessel types is crucial for developing timely mitigation strategies, policies, and penalties. This paper proposes a novel framework for analyzing anomalous events in passageways using Automated Information System (AIS). This framework enables monitoring of affected vessels and quantifies the impact in terms of the number of vessels, dwell and idle times, and the emergence of new routes. To demonstrate its potential, we applied the proposed framework to the Suez Canal blockage in March 2021. Results revealed distinct phases during the event, with each phase impacting average dwell times. Additionally, the analysis identified the emergence of passageway event-driven routes utilized by vessels to bypass the blockage. These findings highlight the ability of the proposed framework to capture previously obscured information compared to existing indicators and port analysis methods. To further demonstrate its generalizability, the methodology was also applied to two other passageways: the Bosporus Strait, following the policy implemented in February 2022 due to the Russian invasion of Ukraine, and the Bab el-Mandeb Strait, following the disruption caused by the Houthi attacks beginning in the last quarter of 2023.